Pengawasan Keimigrasian Kejahatan Transnasional Tindak Pidana Perdagangan Orang (TPPO) di Perbatasan dalam Aspek Kriminologi - Galih Lintang Alam; Masdar Bakhtiar; Alrin Tambunan (Universitas Kapuas, 2025)
Transnational crime, particularly Trafficking in Persons (TPPO), poses a serious threat to national security due to globalization and the ease of cross-border movement. Indonesia's geographical position as an archipelagic state makes it highly vulnerable to this form of modern slavery. This research aims to analyze the vital role of immigration supervision at the border in combating TPPO from a criminological perspective. The research method is qualitative with a normative juridical approach, utilizing a literature study of relevant laws and literature. The results indicate a strong correlation between weak immigration supervision and the rise of TPPO. Indonesia has a legal foundation through its Immigration Law (UU No. 6/2011), Anti-Trafficking in Persons Law (UU No. 21/2007) , and the ratification of the UN Convention Against Transnational Organized Crime. Operationally, countermeasures include administrative and field supervision, the establishment of the